High-temperature sag model for overhead conductors. - Chen, S.L (IEEE Transactions on power delivery)
As electric utilities strive to operate their transmission lines at higher temperatures, several constraints exist that make this goal difficult to achieve. Load may not flow over a desired path, even though the transmission line may have sufficient thermal capacity. Even if system components that allow power to flow over selected circuits are available and in place, there is still an absolute thermal limit placed on an aluminum conductor to prevent annealing of the conductor and excessive sag. This paper describes the combination of a real-time ampacity and a sag/tension program resulting in both a design and operational tool that can be used to predict the instantaneous temperature and sag of a wide variety of conductor designs. The resulting program is specifically designed to predict conductor temperature and sag for temperatures as high as 250°C. The accuracy of the program is evaluated by comparing the predicted sag with the sag measured on two ACSR conductors mounted on a full-scale outdoor test facility. The accuracy of the predicted sag decreases as the average conductor temperature increases. For temperatures less than 150°C, nearly 70% of the time the sag program predicted sags within about 5% of measured values. However, when the conductor temperature was greater than 150°C, the predicted sags were within 5% of the measured values only about 65% of the time.